nov17 - Z 12 / ([ 4 ]) (which in this case is the same as Z...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Math 3124 Thursday, November 17 November 17, Ungraded Homework 1. Problem 39.1 on page 183. Define θ : Z 12 Z 12 by θ ([ a ] 12 ) = [ a ] 4 for each [ a ] 12 Z 12 . (a) Verify θ is well defined. (b) Verify that θ is a homomorphism. (c) Use the Fundamental Homomorphism Theorem for rings to explain why Z 12 / ([ 4 ]) = Z 4 . (d) Construct the Cayley tables for the ring operations on Z 12 / ([ 4 ]) . (a) We need to show that if [ a ] 12 = [ b ] 12 , then θ [ a ] = θ [ b ] , that is [ a ] 4 = [ b ] 4 . However if [ a ] 12 = [ b ] 12 , then 12 | a - b , consequently 4 | a - b and we deduce that [ a ] 4 = [ b ] 4 as required. (b) θ ([ a ] 12 [ b ] 12 ) = θ ([ a + b ] 12 ) = [ a + b ] 4 = [ a ] 4 [ b ] 4 = θ ([ a ] 12 ) θ ([ b ] 12 ) , so θ respects addition. θ ([ a ] 12 ± [ b ] 12 ) = θ ([ ab ] 12 ) = [ ab ] 4 = [ a ] 4 ± [ b ] 4 = θ ([ a ] 12 ) ± θ ([ a ] 12 ) so θ re- spects multiplication. We have now established that θ is a homomorphism. (c) Clearly θ is onto. The fundamental homomorphism theorem for rings now tells us that Z 12 / ker θ = Z 4 , so we need to determine ker θ . But [ a ] 12 ker θ if and only if [ a ] 4 = [ 0 ] 4 , which is if an only if 4 | a , so ker θ = { [ 0 ] 12 , [ 4 ] 12 , [ 8 ] 12 } . This last set is by definition ([ 4 ] 12 ) , so the result is proven. (d) As in problem 22.3 on page 108, we may write the elements of
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Z 12 / ([ 4 ]) (which in this case is the same as Z 12 / h [ 4 ] i ) as 0 = { [ ] , [ 4 ] , [ 8 ] } , 1 = { [ 1 ] , [ 5 ] , [ 9 ] } , 2 = { [ 2 ] , [ 6 ] , [ 10 ] } , 3 = { [ 3 ] , [ 7 ] , [ 11 ] } . Then the Cayley tables will be 1 2 3 1 2 3 1 1 2 3 2 2 3 1 3 3 1 2 and 1 2 3 1 1 2 3 2 2 2 3 3 2 1 2. Problem 39.3 on page 183. Prove that if R is commutative and I is an ideal of R , then R / I is commutative. The general element of R / I is of the form I + a where a R . A ring is commutative means that the operation of multiplication is commutative. Therefore we need to prove that ( I + a )( I + b ) = ( I + b )( I + a ) for all a , b R , in other words I + ab = I + ba for all a , b R . Since R is commutative, we have ab = ba and the result follows....
View Full Document

This note was uploaded on 01/02/2012 for the course MATH 3124 taught by Professor Parry during the Fall '08 term at Virginia Tech.

Ask a homework question - tutors are online